(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The primary concept of the paper is linked with identifying the prospects of nanotechnology in medical science with special attention to human immunodeficiency virus (HIV). The term nano represents extremely small, similarly, the study of nanoscience and nanotechnology is inherently associated with the evaluation of exceptionally small items. These items however are studied within a controlled environment since this helps one to manipulate the phenomena and change their innate properties. Moreover, HIV is ascertained to be a terminal illness which is incurable and higher probability of it leading to AIDS. In compliance with this notion, nanotechnology is deemed vital in altering the dimensions of HIV-affected cells which in turn has a better chance of increased life expectancy. Thereby, this paper attempts to showcase an inherent linkage between the usages of nanotechnology which acts as a therapeutic intervention for HIV.